PENGARUH FASHION INVOLVEMENT DAN SHOPPING LIFESTYLE TERHADAP IMPULSIVE BUYING MAHASISWA POLITEKNIK NEGERI BATAM - Rahmat Hidayat; Inggit Kusni Tryanti (JOURNAL OF APPLIED BUSINESS ADMINISTRATION, 2018)
This research aims to find out how the influence of Fashion Involvement and Shopping Lifestyle in Impulsive Buying of student of Batam State Polytechnic, to find out how far these both of variable affect consumer behavior in Impulsive Buying. This research uses descriptive method that involves 85 business management students as respondents. The data collection is done by questionnaires distribution. Data were analyzed by multiple linier analysis method using SPSS program version 23. The result of partial test showed that Fashion Involvement had a negative but significant effect in Impulsive Buying and Shopping Lifestyle had a positive and significant effect in Impulsive Buying. While the result of the simultaneous test showed that both of variable had a positive and significant effect in Impulsive Buying.